PECULIARITIES OF HEAVY METAL ACCUMULATION IN SOILS IN URBANIZED LANDSCAPES OF BROVARY TOWN - Splodytel, A. O.; Kuraieva, I. V.; Zlobina, K. S. (Institute of Geological Sciences, NAS of Ukraine, 2020)
The regularities of heavy metals distribution in technogenically polluted soils of urbanized territories on the example of the town of Brovary of Kyiv region were analyzed. Physical and chemical properties of conditionally clean and technogenically polluted soils were determined. Regularities of the geochemical distribution of heavy metals in the soil cover of the town under the influence of industrial enterprises were studied. Due to the influence of the Brovary enterprises, heavy metals content is significantly increased in comparison with conditionally clean soils. Using geochemical criteria the technogenic associations of heavy metals in soils were determined. Technogenic associations of heavy metals in soils are represented by the following elements: copper > plumbum > zinc > cobalt > chrome > vanadium > molybdenum > manganese > nickel. The total content level of chemical elements compounds in soils of different zones of the town is heterogeneous. The maximum of the man-caused load was recorded in urban areas of the transport infrastructure zone and the zone of production and communal-warehouse facilities. Copper and plumbum are the main pollutants according to the indices of heavy metals content in soils of anthropogenic zones of the city. Mobile forms of zinc and nickel are the most dangerous soil pollutants at all functional zones of the Brovary. The ecological and geochemical estimation of the total pollution index using Yu.Ye. Saet methodology is performed. The value of this indicator of the soil surface layer in Brovary town (0-10 cm) ranges from 30 to 106, the average value is 65, which corresponds to the dangerous level of contamination of the soil cover. The zones of transport infrastructure and the zones of production and communal-warehouse facilities have high levels of pollution, and the permissible pollution level dominates in the residential zone. According to the concentration ratio of technogenic pollution, the Brovary town belongs to the dangerous category of soil pollution. The investigated soils of the town are characterized by lead geochemical specialization. High levels of zinc, manganese, cobalt and chromium were established. The main factors that influence the concentration levels and heavy metals migration in the town soils were analysed. The dependence of heavy metals content and industrial production objects (factors of anthropogenic load on the natural components of the urban environment) in Brovary was established.